Breaking the classics: Next-generation biosensors for the isolation, profiling and detection of extracellular vesicles - Vaz, Raquel (2022)
Extracellular vesicles (EVs) contain biomarkers that may represent a paradigm shift in timely disease diagnosis and personalized therapeutic approaches. Despite tremendous progress in this field, the considerable complexity and heterogeneity of EVs, combined with hurdles in isolation and accurate characterization, have delayed their envisioned clinical translation. At the same time, emerging biosensor technologies are trying to overcome the limitations and provide new momentum to EVs research. In this review, the focus is given on the variety of novel approaches to improve the capture of EVs of interest from a myriad of sample types in terms of yield, purity, sensitivity, and specificity. These biosensing devices also contribute to the understanding of the content of EVs in correlation with their function. Given the pivotal role of EVs uncovered to date and the recent technological advances discussed herein, nanosensing platforms offer low-cost, fast, simple, and accurate methods that are likely to help gain more insight into the biology of EVs. Moreover, the prospect of identifying new roles and patterns will reinforce the importance of EVs and intercellular communication in health status.